Coupling Mars Ground and Orbital Views: Generate Viewsheds of Mastcam Images From the Curiosity Rover, Using ArcGIS® and Public Datasets. Issue 9 (18th September 2020) - Nachon, M.; Borges, S.; Ewing, R. C.; Rivera‐Hernández, F.; Stein, N.; Van Beek, J. K.
Abstract: The Mastcam (Mast Camera) instrument onboard the NASA Curiosity rover provides an exclusive view of Mars: High‐resolution color images from Mastcam allow users to study Gale crater's geologic terrains along Curiosity's path. These ground observations complement the spatially broader views of Gale crater provided by spacecrafts from orbit. However, for a given Mastcam image, it can be challenging to locate the corresponding terrains on the orbital view. No method for locating Mastcam images onto orbital images had been made publicly available. The procedure presented here allows users to generate Mastcam image viewsheds, using ArcGIS® software, its built‐in Viewshed tool®, and public Mars datasets. This procedure locates onto Mars orbital view the terrains that are observed in a given Mastcam image. Because this procedure uses public datasets, it is applicable to available Mastcam images and to the future ones that will be acquired along the Curiosity rover's path. This procedure can be used by the public to assess scientific questions regarding Martian surface processes and geologic history. In addition, this procedure can be utilized as pedagogic GIS material by the Geosciences or Planetary Sciences communities, for enhancing students' skillsets in GIS and provide students with experience working with datasets from both orbiter and rover Mars missions. Key Points: Mastcam images from the Curiosity rover are available online but lack a public method to be placed back in the Mars orbital context This procedure allows users to generate Mastcam image viewsheds: locate in a map view the Mars terrains visible in Mastcam images This procedure uses ArcGIS® and publicly available Mars datasets